Preparing Emergency Medicine Residents as Teachers: Clinical Teaching Scenarios - Aloysius J. Humbert; Katie E. Pettit; Joseph S. Turner; Josh Mugele; Kevin Rodgers (Association of American Medical Colleges, 2018)
Introduction Preparing residents for supervision of medical students in the clinical setting is important to provide high-quality education for the next generation of physicians and is mandated by the Liaison Committee on Medical Education as well as the Accreditation Council for Graduate Medical Education. This requirement is met in variable ways depending on the specialty, school, and setting where teaching takes place. This educational intervention was designed to allow residents to practice techniques useful while supervising medical students in simulated encounters in the emergency department and increase their comfort level with providing feedback to students. Methods The four role-playing scenarios described here were developed for second-year residents in emergency medicine at the Indiana University School of Medicine. Residents participated in the scenarios prior to serving as a supervisor for fourth-year medical students rotating on the emergency medicine clerkship. For each scenario, a faculty member observed the simulated interaction between the resident and the simulated student. The residents were surveyed before and after participating in the scenarios to determine the effectiveness of the instruction. Results Residents reported that they were more comfortable supervising students, evaluating their performance, and giving feedback after participating in the scenarios. Discussion Participation in these clinical teaching scenarios was effective at making residents more comfortable with their role as supervisors of fourth-year students taking an emergency medicine clerkship. These scenarios may be useful as part of a resident-as-teacher curriculum for emergency medicine residents.